NOTA PREVIA. INCLUSAO DE TECIDOS EM COLA EPOXI COMERCIAL - Vieira Silva, E. C.R.; Gastao Chamma, L. (My University, 1973)
A description is given of a simple inexpensive method for inclusion of animal tissues in commercial epoxy glue. The method permits routine cutting of slices one micron thick in conventional rotating microtomes.
Preliminary report. Inclusion of tissues in commercial epoxi glue